When animals speak toward an interspecies democracy - Meijer, Eva 1980- (Animals in context, 2019)
A groundbreaking argument for the political rights of animals In When Animals Speak, Eva Meijer develops a new, ground-breaking theory of language and politics, arguing that non-human animals speak—and, most importantly, act—politically. From geese and squid to worms and dogs, she highlights the importance of listening to animal voices, introducing ways to help us bridge the divide between the human and non-human world. Drawing on insights from science, philosophy, and politics, Meijer provides fascinating, real-world examples of animal communities who use their voices to speak, and act, in political ways. When Animals Speak encourages us to rethink our relations with other animals, showing that their voices should be taken into account as the starting point for a new interspecies democracy